Profound Transcriptomic Differences Found between Sperm Samples from Sperm Donors vs. Patients Undergoing Assisted Reproduction Techniques Tends to Disappear after Swim-up Sperm Preparation Technique - Sandra García-Herrero; Nicolás Garrido; José Antonio Martínez-Conejero; José Remohí; Antonio Pellicer; Marcos Meseguer (International Journal of Fertility and Sterility, 2010)
Background Although spermatozoa delivers its RNA to oocytes at fertilization, its biological role is not well characterized. Our purpose was to identify the genes differentially and exclusively expressed in sperm samples both before and after the swim-up process in control donors and infertile males with the purpose to identify their functional significance in male fertility. Materials and methods This was a nested case-control study. Ten sperm samples were obtained from infertile patients [n=5 (two aliquots each from five samples; one before the swim-up process and one after)] and donors [n=5 (two aliquots from five samples, one before the swim-up process and one after)]. Oligonucleotide microarrays were employed to study the genome-wide expression of pooled samples from infertile patients vs. donors. A total of four microarrays were perfomed: two with sperm sample aliquots before swim-up and two with sperm samples aliquots after swim-up, from both the case and control groups. The results were evaluated to detect which genes expressed differentially [fold change (FC)>5 and p <0.05] and which genes were exclusive to each of the groups, both before and after swim-up. Results Profound differences were detected between the fresh sperm samples of donors vs. infertile patients with respect to both differentially and exclusively expressed genes. Nevertheless these differences seemed to decrease after the swim-up selection process. Conclusion There are important differences between the expression profiles of sperm samples of fertile donors vs. infertile patients who require assisted reproduction techniques (ART). These differences are potential forecasters of fertility success, although their reliability needs to be explored further.